Revisiting the Principle of Legal Certainty: A Contemporary Analysis through the Lens of Legal Positivism - Itok Dwi Kurniawan; Souad Ezzerouali (NUSANTARA: Journal Of Law Studies, 2024)
The principle of legal certainty, as formulated by Gustav Radbruch, is recognized as one of the essential values of law. It demands that legal rules be written clearly and systematically to avoid ambiguity in interpretation and application. This principle plays a crucial role in ensuring predictability, stability, and public confidence in the legal system. Within the framework of legal positivism—especially in the thoughts of John Austin and Hans Kelsen—clarity, hierarchy of norms, and the separation between law and morality serve as key foundations that strengthen the idea of legal certainty. This study adopts a normative juridical method using a conceptual and philosophical approach. It examines primary legal materials and classical theories of legal positivism to understand how the principle of legal certainty is constructed and justified within positivist reasoning. The findings show that legal certainty functions not only as a procedural guarantee to uphold the rule of law but also as a philosophical reflection of the autonomy and objectivity of the legal system. Furthermore, the study highlights that Radbruch’s theory of values enriches the positivist perspective by introducing a moral dimension to the discourse on legal certainty. The research contributes to the academic discussion by offering a theoretical synthesis between positivist and post-positivist views of legal certainty. This synthesis provides a broader understanding of law as both a normative structure and a moral framework, offering insights that can strengthen the legitimacy and consistency of modern legal systems.